PENGARUH KONSENTRASI KARBOKSIL METIL SELULOSA (CMC) TERHADAP MUTU SIRUP JAMBU METE (Anacardium occidentale L.) - Feri Manoi (Pusat Penelitian dan Pengembangan Perkebunan, 2006)
Effect of Carboxy Methyl Cellulosa Concentration on The Quality of Cashew (Anacardium occidentale L.) SyrupThe stored cashew syrup to plait stiffly deposit and the quality declined. Onecare for prevent this problem to use stabilize material carboxy methyl cellulosa. The experiment was carried out at Village Ekoae, Ende, East Nusa Tenggara since October to November 2004. The objective of the research to find out the best concentration of carboxy methyl cellulosa for the best quality of cashew syrup. This research was laid out a completely randomized design by using four (4) treatments and four (4) repli-cations. The following treatments were use (1) control (no carboxy methyl cellulosa), (2) 0.50% carboxy methyl cellulosa, (3) 1.00% carboxy methyl cellulosa, and (4) 1.50% carboxy methyl cellulosa. The results showed that the use of car-boxy methyl cellulosa with difference concentra-tion had significant effects on observed variable at the stored cashew syrup as long as six week. Carboxy methyl cellulose with 1.50% concen-tration was give the best results and were highest score for pH namely 5.8; with 8.06 mg/100 g of vitamin C and 88.86% of stability.